New Skills in the Changing World of Statistics Education 2020
DOI: 10.52041/iase.20103
|View full text |Cite
|
Sign up to set email alerts
|

Integrating ‘education for sustainable development’ in statistics classes: visual analysis of social and economic data with gapminder

Abstract: Sustainable development goals (SDGs) address various aspects of future human development such as poverty, pollution, or climate change. Education for Sustainable Development (ESD) seeks to encourage students to actively participate and consider these issues in sustainable development. Following design-based research approaches, our study aims to identify opportunities for integrating ESD into statistics education. We describe the main features of an ESD-integrated learning trajectory for middle school students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Several of these studies used interdisciplinary learning environments addressing authentic problems and including real-world datasets. This approach has been shown to be effective in developing students' knowledge of statistical concepts (Andre et al, 2020) and their ability to ask and answer databased questions (Swan et al, 2013;Vahey et al, 2012). Furthermore, increases in students' confidence in data analysis and statistical skills (such as data management and data analysis; Dierker et al, 2017) as well as positive effects on students' interest in data (Kochevar et al, 2015) have been found.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Several of these studies used interdisciplinary learning environments addressing authentic problems and including real-world datasets. This approach has been shown to be effective in developing students' knowledge of statistical concepts (Andre et al, 2020) and their ability to ask and answer databased questions (Swan et al, 2013;Vahey et al, 2012). Furthermore, increases in students' confidence in data analysis and statistical skills (such as data management and data analysis; Dierker et al, 2017) as well as positive effects on students' interest in data (Kochevar et al, 2015) have been found.…”
Section: Resultsmentioning
confidence: 97%
“…A common feature of most of the approaches listed in Table 1 is the integration of digital media. The usage of specific software (e.g., Gapminder in Andre et al, 2020;Jiang et al, 2020) and novicefriendly web-based interfaces (Kochevar et al, 2015;Mosquera et al, 2020;Wolff et al, 2019) has been demonstrated to be effective in helping students deal with large and complex real-world data sets.…”
Section: Resultsmentioning
confidence: 99%